Carbon Dioxide as a Tool to Deter the Movement of Invasive Bigheaded Carps. Issue 3 (27th April 2016) - Donaldson, Michael R.; Amberg, Jon; Adhikari, Shivani; Cupp, Aaron; Jensen, Nathan; Romine, Jason; Wright, Adam; Gaikowski, Mark; Suski, Cory D.
Abstract: Nonnative bigheaded carps are established in the Mississippi River and there is substantial concern about their potential entry into the interconnected Laurentian Great Lakes. While electrical barriers currently exist as a preventative measure, there is need for additional control mechanisms to promote barrier security through redundancy. We tested the effectiveness of infused carbon dioxide gas (CO2 ) as a tool to influence the movement and behavior invasive bigheaded carps, namely Bighead Carp Hypophthalmichthys nobilis and Silver Carp H. molitrix, as well as native Bigmouth Buffalo Ictiobus cyprinellus, Channel Catfish Ictalurus punctatus, Paddlefish Polyodon spathula, and Yellow Perch Perca flavescens in an experimental pond. Individuals were monitored with acoustic telemetry before, during, and after CO2 addition to the pond. We noted distinct changes in fish behavior following CO2 addition. Each species except Paddlefish maintained farther distances from the CO2 infusion manifold relative to controls. Both bigheaded carp species had slower persistence velocities (persistence of a movement in a given direction) following CO2 infusion and Bighead Carp used a smaller area of the pond immediately after CO2 addition. Pond pH progressively decreased up to 1.5 units following CO2 infusion. This work provides evidence that could inform future research to enhance existing control measures used to deter high‐risk invasive fishes, such as bigheaded carps. Received July 27, 2015; accepted January 11, 2016 Published online April 27, 2016